Spontaneous reports of vasculitis as an adverse event following immunization: A descriptive analysis across three international databases. Issue 51 (12th December 2016) - Felicetti, Patrizia; Trotta, Francesco; Bonetto, Caterina; Santuccio, Carmela; Brauchli Pernus, Yolanda; Burgner, David; Chandler, Rebecca; Girolomoni, Giampiero; Hadden, Robert D.M.; Kochhar, Sonali; Kucuku, Merita; Monaco, Giuseppe; et al.
Highlights: Similar results in three database. Vasculitis was mainly reported in children. Case definitions would improve data quality and comparability. Abstract: Background: Vasculitides have been reported as adverse events following immunization (AEFI) following various vaccines. We describe reports of vasculitis to three international spontaneous reporting systems. Methods: All spontaneous reports of vasculitis following immunization between January 2003 and June 2014 were retrieved from Eudravigilance (EV), the Vaccine Adverse Event Reporting System (VAERS), and VigiBase ® . A Standard MedDRA Query (SMQ) for vasculitis was used and vaccine types were categorized using the Anatomical Therapeutic Chemical classification system. We performed a descriptive analysis by source, sex, age, country, time to onset, vaccine, and type of vasculitis. Results: We retrieved 1797 reports of vasculitis in EV, 1171 in VAERS, and 2606 in VigiBase ® . Vasculitis was predominantly reported in children aged 1–17 years, and less frequently in the elderly (>65 years). The generic term "vasculitis" was the most frequently reported AEFI in this category across the three databases (range 21.9% to 27.5% of all reported vasculitis for vaccines). For the more specific terms, Henoch–Schoenlein Purpura (HSP) was most frequently reported, (19.1% on average), followed by Kawasaki disease (KD) (16.1% on average) and polymyalgia rheumatica (PMR) (9.2% on average). Less frequently reported subtypes were cutaneous vasculitis (CuV), vasculitis of the central nervous system (CNS-V), and Behcet's syndrome (BS). HSP, PMR and CuV were more frequently reported with influenza vaccines: on average in 29.3% for HSP reports, 61.5% for PMR reports and in 39.2% for CuV reports. KD was reported with pneumococcal vaccines in 32.0% of KD reports and with rotavirus vaccines in more than 20% of KD reports. BS was most frequently reported after hepatitis and HPV vaccines and CNS-V after HPV vaccines. Conclusion: Similar reporting patterns of vasculitides were observed in different databases. Implementation of standardized case definitions for specific vasculitides could improve overall data quality and comparability of reports.